IL17-deficient NOD mice are protected from autoimmune diabetes due to decreased antigen presentation and T cell activation - Pearson, James A.; Li, Yangyang; Huang, Juan; Peng, Jian; Wong, F. Susan; Wen, Li (Frontiers in Immunology, 2026)
IntroductionIL-17 is a key cytokine helping preserve the intestinal barrier against infections; however, the T cells that primarily secrete IL-17 (Th17) can promote the development of autoimmunity. In Type 1 diabetes, the role of IL-17 is less well understood, with many studies evaluating the role of IL-17, without considering changes within the intestine. Furthermore, therapeutically targeting IL-12/IL-23 (upstream of IL-17) or IL-17 directly can help preserve insulin-producing beta cells in those newly diagnosed with Type 1 diabetes. Thus, there is a need to better understand how IL-17 may modulate susceptibility to Type 1 diabetes by linking intestinal changes to type 1 diabetes development.MethodsWe studied IL-17-deficient NOD mice to understand the role of IL-17 in mediatingsusceptibility to Type 1 diabetes in vivo and in vitro.ResultsOur study showed that IL-17-deficient NOD mice were protected from autoimmune diabetes, and in vivo adoptive transfer studies showed that both immune and non-immune cells are important for modulating diabetes development. We found significant reductions in both regulatory T cells and inflammatory T-bet-expressing CD8+ T cells, while Type 3 Innate Lymphoid Cells (ILC3s) were expanded. These changes were found to be mediated through altered gut microbiota composition of the IL-17-deficient NOD mice. Finally, we demonstrated that intestinal epithelial cells from IL-17-deficient NOD mice were less able to present autoantigen to autoreactive CD8+ T cells, with reduced proinflammatory cytokine secretion. This effect was specific to IL-17 deficiency, as addition of exogenous IL-17 resulted in improved antigen presentation to autoreactive CD8+ T cells.DiscussionTogether, our data suggest a novel role for IL-17 in modulating epithelial cell function and antigen presentation within the intestinal tissue, resulting in reduced autoantigen-specific T cell responses and enhanced protection from autoimmune diabetes. Better understanding of how targeted IL-17 blockade could be administered to the intestine may help better prevent the development of Type 1 diabetes.